ICT Diffusion in Developing Countries: Towards a New Concept of Technological Takeoff - Lechman, Ewa (Springer, 2015)
This book provides an extensive overview of the diffusion of Information and Communication Technologies (ICTs) in developing countries between 2000 and 2012. It covers issues such as country-specific ICT diffusion patterns, technological substitution and technological convergence. By identifying social, economic and institutional prerequisites and analyzing critical country-specific conditions, the author develops a new approach to explaining the emergence of their technological takeoff. Readers will discover how developing countries are now adopting ICTs, rapidly catching up with the developed world in terms of ICT access and use.